2019
DOI: 10.1096/fj.201802251r
|View full text |Cite|
|
Sign up to set email alerts
|

Lunasin attenuates oxidant‐induced endothelial injury and inhibits atherosclerotic plaque progression in ApoE−/−mice by up‐regulating heme oxygenase‐1viaPI3K/Akt/Nrf2/ARE pathway

Abstract: Oxidative stress–induced vascular endothelial cell (VEC) injury is a major mechanism in the initiation and development of atherosclerosis. Lunasin, a soybean‐derived 43‐aa peptide, has been previously shown to possess potent antioxidant and anti‐inflammatory activities other than its established anticancer activities. This study investigated the effects of lunasin on protecting VECs from oxidative damage and inhibiting atherosclerotic plaque progression in apolipoprotein E–deficient (ApoE−/−) mice and explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…However, the phosphorylation levels of the Akt protein were increased upon RSV treatment in our study. The PI3K/Akt signaling pathway is commonly involved in the Nrf2-dependent transcription in diverse cell types of responding ROS insults [37, 38]. Han's study showed that chlorogenic acid protects MC3T3-E3 cells against oxidative stress through the PI3K/Akt-mediated Nrf2 signaling pathway to induce HO-1 expression, suggesting that Nrf2 may be a downstream signal target of PI3K/Akt [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the phosphorylation levels of the Akt protein were increased upon RSV treatment in our study. The PI3K/Akt signaling pathway is commonly involved in the Nrf2-dependent transcription in diverse cell types of responding ROS insults [37, 38]. Han's study showed that chlorogenic acid protects MC3T3-E3 cells against oxidative stress through the PI3K/Akt-mediated Nrf2 signaling pathway to induce HO-1 expression, suggesting that Nrf2 may be a downstream signal target of PI3K/Akt [19].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PI3K/Akt and up-regulation of heme oxygenase-1 (HO-1) might be new targets for inhibiting ox-LDL-induced apoptosis. Lunasin (Figure 1) is upregulated through the PI3K/Akt/Nrf2/antioxidant response element (ARE) pathway, and HO-1, attenuated oxidative-induced endothelial injury and inhibits the progression of atherosclerotic plaques in ApoE −/− mice (Gu et al, 2019). Clinical trials have shown that the PI3K/Akt/Nrf2 signaling pathway plays an important role in cardiovascular cell antioxidants mediated by the metabolite S-(-) equol, which is derived from soybean isoflavones (Zhang et al, 2013).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…For example, the Nrf2 -/mice promoted the happening of more oxidative stresses that induced the evolution of NAFLD to NASH comparing with the WT mice [15]. Recent studies have shown that many small molecule compounds play the functions of anti-inflammatory, antioxidative stress, and antiapoptosis by activating PI3K/Akt/Nrf2 signal [16][17][18]. Some studies have found that S-propargyl-cysteine can protect MCD-induced fatty liver by the activation of Akt/Nrf2/HO-1 pathway [19].…”
Section: Introductionmentioning
confidence: 99%